Effects of differences in age and body height on normal values of central motor conduction time determined by F-waves. (4th March 2017) - Imajo, Yasuaki; Kanchiku, Tsukasa; Suzuki, Hidenori; Yoshida, Yuichiro; Funaba, Masahiro; Nishida, Norihiro; Fujimoto, Kazuhiro; Taguchi, Toshihiko
Abstract : Objectives : To investigate the effect on central motor conduction time (CMCT) based on the relationship between age and height in normal subjects. Design : Retrospective study. Methods : One hundred and ninety nine normal subjects (107 men and 92 women; mean age 39.0 ± 16.4 years; mean height 164.5 ± 8.8 cm) participated in the study. The approximate ages of subjects were as follows: 82 (20–29 years old), 32 (30–39 years old), 32 (40–49 years old), 28 (50–59 years old), and 25 (≧60 years old). The heights of 9, 49, 79, 53, and 9 subjects were <150 cm, 150–160 cm, 160–170 cm, 170–180 cm, and >180 cm, respectively. CMCT- abductor digiti minimi (ADM) and abductor hallucis (AH) were calculated by subtracting the peripheral motor conduction time (PMCT) from the onset latency of motor evoked potentials (MEPs) evoked by transcranial magnetic stimulation. PMCT was calculated from the latencies of the compound muscle action potentials (CMAPs) and F-waves as follows: (latency of CMAPs + latency of F-waves -1)/2. Outcome measures : CMCT-ADM and CMCT-AH. Results : The normative values were 5.2 ± 0.8 ms and 11.8 ± 1.3 ms for CMCT-ADM and CMCT-AH, respectively. CMCT-ADM was not significantly correlated with age (P = 0.196) and body height (P = 0.158). CMCT-AH had significantly positive, linear correlations with age and body height (CMCT-AH = 0.014 × age + 10.971, P = 0.011, R = 0.179 and CMCT-AH = 0.026 × body height + 7.158, P = 0.010, R = 0.182). Conclusions : We suggest normative values of 3.2–7.2 ms in CMCT-ADM for subjects exerting slight effort on ADM regardless age and body height. CMCT-AH had significantly positive, linear correlations with age and body height.